1082. Meta-Analysis of Survival Outcomes in People Who Inject Drugs After Cardiac Surgery for Infective Endocarditis. (26th November 2018) - Goodman-Meza, David; Weiss, Robert E; Gamboa, Sebastián; Gallegos, Abel; Landovitz, Raphael J; Bui, Alex A T; Goetz, Matthew B; Shoptaw, Steven
Abstract: Background: The United States' opioid epidemic has led to an increase in people who inject drugs (PWID) and opioid-associated infections, including infectious endocarditis (IE). Cardiac surgery is often indicated in IE to improve outcomes but is controversial in PWID due to the concerns about continued injection drug use leading to risk for reinfection and decreased survival. In response, we assessed the long-term survival after cardiac valve surgery in PWID compared with people who do not inject drugs (non-PWID) in the published literature. Methods: We performed a systematic review and meta-analysis (MA) of studies that reported survival data after surgery for IE in PWID. We searched PUBMED up to April 2018. We extracted Kaplan–Meier (KM) curves from included studies. From the KM curves, we used an algorithm to estimate individual participant data (eIPD). In a one-step approach, we ran a Cox proportional hazards (CPH) model analysis of the eIPD with study random effects. In a two-step approach, we fitted CPH models by individual study; then, we ran a mixed-effects MA model of the log hazard ratios (HR) and standard errors. Results: We identified 11 retrospective studies. Of these, six reported comparisons of PWID vs. non-PWID, and five reported results for PWID only. Based on eIPD, we included 407 PWID and 1, 877 non-PWID. Mean age for PWID was 36.7 years (95% CI 34.4–39.1) and for non-PWID was 52.0 years (95% CI 45.3–59.4). There were 144 deaths (35.3%) in PWID and 559 (29.8%) deaths in non-PWID. We present by study and by group KM curves of eIPD (Figures 1 and 2). In one-step MA (included all 11 studies), the HR for PWID was 1.13 (95% CI 0.92–1.39). In two-step MA (included six comparison studies), heterogeneity was high ( I 2 = 72%); and there was no significant between-group difference (HR 1.29, 95% CI 0.80–2.07) (Figure 3). Conclusion: Survival time post-surgery of PWID was similar to that of non-PWID. These estimates are concerning, as PWID on average are much younger than non-PWID with IE. Future studies should explore interventions to improve outcomes in PWID after surgery, including treatment of addiction during and after the index hospitalization and provision of naloxone at the time of discharge. Disclosures: All authors: No reported disclosures.